2022
DOI: 10.5539/ijps.v14n1p21
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Organizational Factors on Registered Nurses’ Work Attitudes in Nigeria

Abstract: This study examined the influence of competence development, work-life balance, perceived organizational support and organization’s commitment to employees on job satisfaction, affective commitment and turnover intention among registered nurses in Nigeria’s Ondo State. The sample consisted of 220 registered nurses from six public hospitals in Ondo State. Data analysis was conducted using multivariate regressions, Pearson’s product-moment correlation and descriptive statistics to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…Support for work-life balance, improved pay, and increasing the HCW labor force is recommended to strengthen the system. 38,39 These findings correspond to a global study conducted prior to the pandemic, which also showed that…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Support for work-life balance, improved pay, and increasing the HCW labor force is recommended to strengthen the system. 38,39 These findings correspond to a global study conducted prior to the pandemic, which also showed that…”
Section: Discussionsupporting
confidence: 88%
“…Support for work-life balance, improved pay, and increasing the HCW labor force is recommended to strengthen the system. 38 , 39 …”
Section: Discussionmentioning
confidence: 99%